EFEKTIVITAS PRA PERADILAN DALAM RANGKA PERLINDUNGAN HAK ASASI MANUSIA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1981 TENTANG KITAB UNDANG-UNDANG HUKUM ACARA PIDANA DI WILAYAH HUKUM PENGADILAN NEGERI BENGKALIS - DANIEL SITORUS; Erdiianto '; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The dynamiics of tthe probllems tthatt ariise regardiing tthe applliicattiion of e-IDcard fiirstt so many probllems tthere are iindiicattiions iin tthe proviisiion of e-ID cardprojjectt Such corrrupttiion,, tthe second probllem iis tthe factt tthatt quiitte iintteresttiing tthatttthe refusall by some priivatte banks iin Indonesiia wiitth tthe reason tthe E-ID card KTPiis nott tthe same as tthe previious,, tthe tthiird probllem iis:: Based on tthe mandatte ofArttiiclle 63 Paragraph (3) of Law No.. 23 Year 2006 concerniing PopullattiionAdmiiniisttrattiion Ellecttroniic Identtiitty Card (e-ID) applliies nattiionalllly,, butt iin tthe caseprakttenya ttersbutt diiffiiculltt tto embodiied,, whiille tthe fourtth iissue iis ttheiimpllementtattiion of e-ID card lliifettiime.. Of tthe four iissues above autthors wriittiingtthesiis proposall iis focused on tthe probllems tthatt allll tthiird and fourtth course tthiis hasa correllattiion wiitth tthe autthor angkatt..Inii ttiittlle tthatt attttractts wriitters tto lliiftt tthe ttiittlle::